Implementing Civic Culture to Improve Students' Environmental Awareness at SMPN 1 Bayan - Gustia, Mila; Zubair, Muh.; Alqadri, Bagdawansyah; Basariah, Basariah (Jurnal Penelitian Medan Agama, 2025)
This study examines the implementation of civic culture in improving students' environmental awareness at SMPN 1 Bayan, North Lombok, as a response to the low awareness of cleanliness and discipline in waste management. Descriptive qualitative method was used involving 6 students, 2 teachers, and 1 principal as subjects. Data were collected through interviews, observations, and documentation, then analyzed thematically. The results showed that the integration of civic culture (knowledge, skills, and attitudes of citizenship) through the "Clean Saturday" program, environment-based Civics learning, and teacher exemplification succeeded in increasing student participation: 90% consistently throw garbage in its place, 85% are active in cleaning activities, and the emergence of initiatives to care for plants. However, 15-20% of students still lack discipline without supervision. Supporting factors include school facilities (15 segregated bins, 3 parks), parental support, and a culture of gotong royong, while the main obstacle is the lack of intrinsic awareness of some students. The research conclusion confirms that civic culture is effective in shaping the character of environmental care through a holistic approach, with recommendations for strengthening the habituation program and community collaboration.